THE READINESS OF PRIMARY SCHOOL TEACHERS TO IMPLEMENT THE READ-ANSWER-DISCUSS-EXPLAIN- AND CREATE (RADEC) LEARNING MODEL (International Conference on Elementary Education, 2018)
This study aims to investigate the primary school teachers? readiness to implement Read-Answer- Discuss-Explain-and Create (RADEC) learning model. This research was a survey research with quantitative approach. 32 primary school teachers in the Sub-district of Pagerageung, Tasikmalaya Regency, West Java participated in this study. They have already attended the workshop on RADEC Learning Model. Data were collected by using questionnaire. Data analysis used percentage technique with editing, scoring, and tabulation stage. The results show that the primary school teachers are ready to implement the RADEC learning model. Based on readiness aspects, the gain of Cognitive aspect readiness is in the Very Ready category, the gain of Emotive-attitudinal aspect readiness is in the Very Ready category, and the gain of Behavioral aspect readiness is in the Ready category. However, there is an indicator on the Behavioral aspect readiness, namely organizing time, still in the Less Ready category. This means the teachers may have difficulty to take time trying RADEC learning model.